Organizational Structure from Interaction: Evidence from Corporate Sustainability Efforts. (March 2020) - Soderstrom, Sara B.; Weber, Klaus
We advance interactionist perspectives on how organizational structures emerge in new issue domains. Our study is grounded in field data collected over 18 months at a large biomedical company that sought to become more sustainable. Over that period, some sustainability-related issues became firmly embedded in formal structures and procedures, while others faltered. We identify the quality of situational interactions among organizational members as the engine behind the structuring of organizational sustainability efforts. Successful interactions generated traces of attention, motivation, knowledge, relationships, and resources that linked fleeting interactions to emergent organizational structures. Our findings point to the importance of internal advocates and distributed processes at middle and lower levels for developing organizational structures, and we show that advocates' interests, commitments, and identities are altered in the course of repeated interactions, as are the political resources available to them. Paying attention to situation-level interactions thus results in a more dynamic view of the emergence of formal structures through political processes. We develop a process model that informs structuration perspectives on organizational change by showing how social interaction dynamics can account for divergent levels of structuring within the same domain. The model also advances political perspectives on organizational change by unpacking the situational underpinnings of advocacy efforts and collective mobilization around issues.